The Administration for Community Financial Institution through Participation of Community Member in Udon Thani Province - Hinkaew, Theerawat (Rajamangala University of Technology Tawan-ok Social Science Journal, 2025)
The objectives of this research were to study the management and recommendations and guidelines for the management of community financial institutions with participation of community members at Nonghan District, Udon Thani Province, Thailand. This research was a combination of methods such as qualitative research using interview form. Data were analyzed from in depth interviews from 31 key informants and quantitative questionnaires using a questionnaire. Data were collected from a sample 375 subjects, who were sampled using the ready-made tables of Crazy and Morgan. The statistics used for data analysis were mean, frequency and percentage values. The results of the research were as following: 1) Community financial institution management with participation of Nonghan District, Udon Thani Province Overall, it was at a high level (x ̅ = 4.37, S.D. = 0.68) and sorted from highest to lowest as follows: community deposit aspect (x ̅ = 4.82, S.D. = 0.42), financial counseling aspect (x ̅ = 4.77, S.D. = 0.49), promotion of community savings aspect (x ̅ = 4.68, S.D. = 0.58), community welfare aspect (x ̅ = 4.03, S.D. = 0.52) and credit to member aspect (x ̅ = 3.56, S.D. = 0.49). 2) Recommendations and guidelines for community financial institution management by participation of member of Nonghan District Udon Thani Province found that financial institution should be a variety of deposit services. The reward should be given to members who open a savings account for the first time as a morale booster and depository clerks must be honest. Community financial institutions should have consultants to help solve problems and should develop deposits through smartphone applications. The interest in applying for a loan should be cheaper more than another banks; moreover, institution should recommend financial planning for members and further sustainable career development to provide income-generating opportunities for members such as a children’s lunch fund, Children’s education fund, funeral provident fund and provident fund for the member’s Children from birth to six years.